(untitled) (UNED Research Journal, 2020)
Introduction: Many land molluscs survival strategies are still poorly understood or have not been even reported, especially in the Neotropics. Methods: I collected 25 adult Tikoconus (Tikoconus) costarricanus from Reserva Forestal Río Macho, Costa Rica. I kept the specimens for 8 days in terrariums to film their behavior. Objective: To analyse the behavior of T. costarricanus, with emphasis on its strategies to survive drought and probably also predation. Results: This snail has at least three unusual behaviors that probably help them reduce dehydration and may be escape from enemies and avoid diseases: hanging upside down like bats, falling and grooming. During aestivation, they compress the body and hang upside down from leaves, like bats hang from perches. They attach to the underside of leaves with mucus from a caudal gland. Disengagement is done with vigorous shell rotations and foot twisting in contorting sequences, and can be done as reaction to direct sunlight, and probably to avoid predators and parasites. They groom their own shell, shell lappets and foot, an unusual behavior among land snails. This species feeds mainly on epiphyllous mosses, algae and lichens, occasionally adding arthropod eggs and carrion. Egg laying is similar to other euconulids and valloniid snails. Conclusions: Aestivating hanging upside down is a drought avoiding trait described here for the first time and is also a new function for the caudal gland mucus. Leaf detaching is done by a contortion sequence of shell rotations and foot twisting; its complexity and duration varies according to the leaf side where the snail is located.